Republic of Turkey (Washington, D.C.)
1 mikrofiş (7 poz)
Keywords: Includes basic statistical data on Turkey's population, labor force in agriculture, "agricultural land," per capita gross national product, exports, education, and health (infant mortality, life expectancy, people per physician).